Vision screening battery for children with learning disabilities in special education classes in the government primary schools / Nurul Farhana Abu Bakar - Abu Bakar, Nurul Farhana (2013)
A validated vision screening battery is essential to efficiently identify those with vision problems for prevention and early intervention. The use o f single-test design o f Snellen notation distance acuity testing in our national vision screening program might not be appropriate for children with learning disabilities in primary schools due to communication difficulties and intellectual discrepancies. The main purpose o f this study was to determine a suitable vision screening battery for children with learning disabilities in special education classes in government primary schools in Malaysia. To achieve that, four aspects were investigated which include gathering information on common vision disorders among children with learning disabilities in government primary schools, identifying appropriate personnel as potential vision screener, evaluation o f suitable vision screening tests as well as testing the sensitivity and specificity o f the proposed vision screening approach. Refractive error, strabismus, convergence insufficiency and accommodative response anomaly were found as common vision disorders in children with learning disabilities in government primary schools. Review on the issue on personnel suggested that nurses and assistant medical officers could be the choice as vision screener. The Cambridge Crowding Cards, the Lang II Stereotest and the modified version o f COVD-QOL questionnaire were among the suitable choices o f vision tests for children with learning disabilities. The use o f the two-level vision screening approach is recommended for children with learning disabilities in schools due to its high testability, high validity to detect important vision disorders, simplicity and cost effectiveness.